P534Central sleep apnea in pacing-induced cardiomyopathy: prevalence, improvement by upgrading to cardiac resynchronisation therapy and impact on structural responder rates and long-term outcome. (18th June 2020) - Barbieri, F; Adukauskaite, A; Heidbreder, A; Brandauer, E; Bergmann, M; Senoner, T; Rubatscher, A; Schgoer, W; Stuehlinger, M; Pfeifer, B; Bauer, A; Hintringer, F; et al.
Abstract: Funding Acknowledgements: ÖNB Jubiläumsfondsprojekt Nr. 15974, ISR grant by Boston Scientific, St. Paul, MN, USA Background: Central sleep apnea (CSA) in pacing induced cardiomyopathy (PICM) is poorly studied. Specifically, it is unknown whether upgrading from right ventricular pacing (RVP) to cardiac resynchronisation therapy (CRT) improves CSA. Methods: Fifty-three patients with impaired left ventricular ejection fraction, frequent right ventricular pacing due to high-grade atrioventricular block and heart failure symptoms despite optimal medical therapy underwent upgrading to CRT. Within one month after left ventricular lead implantation (but still not activated), sleep apnea was assessed in all participants by single-night polysomnography (PSG). Nineteen patients with moderate or severe CSA defined by an apnea hypopnea index (AHI) > 15 events per hour were re-scheduled for a follow up PSG 3-5 months after initiation of cardiac resynchronization therapy. Of this cohort, thirteen patients with stable mild heart failure agreed to be randomized to CRT versus RVP in a cross-over design. Results: CSA (AHI > 5 events per hour) was diagnosed in 26 (49.1%), OSA in 16 (30.2%) patients suffering from PICM . Eleven (20.8%) patients did not have any form of sleep apnea. Moderate to severe CSA (AHI > 15 events per hour) was significantly improved (without specific CPAP therapy) by 102 (96-172) days of CRT: AHI decreased from 39.4 events per hour at baseline to 21.6 by CRT (p < 0.001). Furthermore, CRT led to a substantial decrease in left ventricular endsystolic volumes: baseline 141 ml (103-155), significant improvement under CRT (102 ml, 65-138; p < 0.001), whereas no effect with ongoing RV-pacing (147 ml, 130-161; p = 0.865). Preexistent CSA did not affect the structural response of CRT (56.5% in patients with CSA, 62.5% of patients with obstructive sleep apnea and 54.5% in patients without sleep apnea; p = 0.901) and had no impact on major adverse cardiac events (p = 0.412) and/or survival (p = 0.623) during long-term follow-up. Conclusions: CSA is highly prevalent in patients with PICM and is significantly improved by upgrading to CRT. Preexistent CSA does not hamper structural improvement and long-term outcome after upgrading to CRT. Thus, CSA seems to occur as a consequence of PICM, rather than as a pathophysiological mediator.